PENGARUH MOTIVASI BELAJAR EKSTRINSIK, PERILAKU BELAJAR, DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI AKADEMIK MAHASISWA (STUDI PADA MAHASISWA STIE INDONESIA BANKING SCHOOL ANGKATAN 2021 - 2023) - Prameswari, Ebita; Wardani, Deni (Journal of Accounting, Management and Islamic Economics, 2024)
In the era of globalization, various complex challenges arise and require solutions. One solution is to improve the quality of human resources which are influenced by various factors, including skills and competencies. Fresh graduates who are not only disadvantaged but also face challenges in finding a job are often considered fresh graduates. In Indonesia, the concept of fresh graduate is very complex and multidimensional, with many graduates pursuing higher education and adapting to the new work environment. The success of fresh graduates depends on a variety of factors, including the quality of education and the quality of the learning environment. The achievement of academic success can be influenced by a variety of factors, including the quality of education and the quality of the learning environment. External factors, such as society, and academic life, play an important role in providing adequate support and making students feel valued. Internal factors, such as the quality of learning activities, also play an important role in determining the success of fresh graduates. The type of research used in this study is primary data using a survey method with questionnaires to collect data directly from respondents and secondary data is information that has been collected and processed by other parties and can be obtained from various sources such as books, the internet, and scientific journals that are relevant to the research topic. Hypothesis testing in this study uses the PLS or Partial Least Square method with SmartPLS 4.0 software. The results showed that Extrinsic Learning Motivation has no effect on Academic Achievement, Learning Behavior had a positive effect on Academic Achievement, and Learning Environment had a positive effect on Academic Achievement.